2004
DOI: 10.1074/jbc.m407229200
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Extrasynaptic GABAA Receptors Modulates Tonic Inhibition in Cultured Hippocampal Neurons

Abstract: Tonic inhibition plays a crucial role in regulating neuronal excitability because it sets the threshold for action potential generation and integrates excitatory signals. Tonic currents are known to be largely mediated by extrasynaptic ␥-aminobutyric acid type A (GABA A ) receptors that are persistently activated by submicromolar concentrations of ambient GABA. We recently reported that, in cultured hippocampal neurons, the clustering of synaptic GABA A receptors significantly affects synaptic transmission (Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 84 publications
(105 reference statements)
2
42
0
Order By: Relevance
“…This conclusion is consistent with studies in developing and mature cerebellum that showed a clear link between sIPSCs and tonic currents mediated by ambient GABA (Brickley et al 1996;Carta et al 2004;Kaneda et al 1995;Wall and Usowicz 1997). It is also consistent with cell culture studies of both cerebellar and hippocampal neurons that show TTX-mediated reductions in tonic GABAergic currents (Leao et al 2000;Petrini et al 2004) and with in vitro work in hippocampus directly implicating KA-induced increases in sIPSCs with GABA A -mediated changes in holding current (Frerking et al 1999). Nevertheless, it is clear that action potential-independent mechanisms for regulating ambient GABA have also been implicated in some studies (Rossi et al 2003;Wall and Usowicz 1997).…”
Section: Direct and Indirect Inhibition Of Minimally Evoked Epscssupporting
confidence: 80%
See 1 more Smart Citation
“…This conclusion is consistent with studies in developing and mature cerebellum that showed a clear link between sIPSCs and tonic currents mediated by ambient GABA (Brickley et al 1996;Carta et al 2004;Kaneda et al 1995;Wall and Usowicz 1997). It is also consistent with cell culture studies of both cerebellar and hippocampal neurons that show TTX-mediated reductions in tonic GABAergic currents (Leao et al 2000;Petrini et al 2004) and with in vitro work in hippocampus directly implicating KA-induced increases in sIPSCs with GABA A -mediated changes in holding current (Frerking et al 1999). Nevertheless, it is clear that action potential-independent mechanisms for regulating ambient GABA have also been implicated in some studies (Rossi et al 2003;Wall and Usowicz 1997).…”
Section: Direct and Indirect Inhibition Of Minimally Evoked Epscssupporting
confidence: 80%
“…However, such measurements must be carefully obtained to prevent contamination by sIPSCs (Prenosil et al 2006;Scimemi et al 2005). Alternatively tonic currents have been characterized using noise analysis (Brickley et al 1996;Mtchedlishvili and Kapur 2006) or by fitting a Gaussian curve to an all-points histogram of sampled data (Glykys and Mody 2006a;Glykys et al 2006;Petrini et al 2004;Wall and Usowicz 1997). Unfortunately, these techniques generally fail to simultaneously describe changes in both tonic and phasic currents.…”
Section: Independent Measurement Of Phasic and Tonic Currents From Comentioning
confidence: 99%
“…Beta subunits could escape such ER trapping because mutation of R43 of the ␥2 subunit is thought to modify interactions with ␤ but not ␣ subunits (Hales et al, 2005). Alternatively, mutant R43Q ␥2 may compete for ␣5-associated proteins, such as radixin (Loebrich et al, 2006), and so prevent aggregation of extrasynaptic receptors thus decreasing tonic inhibition (Petrini et al, 2004). Tonic GABA currents of hippocampal pyramidal cells are probably mediated by both ␣5␤3␥2 and ␣4␤2/3␦ assemblies, in proportions that may depend on agonist concentration (Caraiscos et al, 2004;Scimemi et al, 2005;Glykys and Mody, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of GABA A Rs could be observed on neuronal processes. These were either co-localised with synaptotagmin and thus considered to be synaptic, or were otherwise considered to be extrasynaptic (39,40). Diffuse labelling was also present, likely reflecting the existence of a mobile extrasynaptic GABA A R population (41).…”
Section: Accepted Manuscriptmentioning
confidence: 99%